Análise da simultaneidade das proxies de qualidade das informações contábeis - Duarte, Filipe Coelho de Lima (2016)
The objective of this paper was to analyze how the relation between the simultaneity of proxies of the earnings quality. It was sought to achieve this goal through the formulation of an empirical model of structural equations based on evidence presented by the review of literature about the earnings quality. The sample used in this study included the firms that traded shares in the US capital market from 1985 to 2015. It was used as proxies for earnings quality consolidated according to Dechow, Ge and Schrand (2010), which was earnings management used by Paulo (2007), quality of accruals (DECHOW; DICHEV, 2002) and value relevance by the model of prices (COLLINS; MAYDEW; WEISS, 1997), while for firms chacarteristics were used total debt and firm size. The initial results obtained by multiple linear regression showed, in general, that for the proxies quality of the accruals and value relevance the relations of the characteristics of the firms were presented according to the evidences of the literature (DECHOW; GE; SCHRAND, 2010); While for earnings management, the firm size relationship was positive, contrary to the literature. Regarding the measurement of the quality of information as a latent variable, that is, incorporating all the dimensions analyzed, the relationships corroborated the evidence pointed out in the literature, that is, the management of results reduced the quality of the accounting information and the quality of accruals and value relevance increased, whereas size was positively related to the earnings quality, while debt negatively impacted the quality of accounting information. Regarding the quality of the adjustment statistics, they did not meet the satisfactory statistical requirements, according to Marôco (2010), for validation of the tested model. Thus, measuring the earnings quality simultaneously by structural equations produces the effects capable of explaining the quality of accounting information as a latent variable when realigned with the characteristics of firms.